Passive remediation of acid mine drainage using cryptocrystalline magnesite: A batch experimental and geochemical modelling approach - Masindi, V.; Gitari, M.W.; Tutu, H.; De Beer, M. (South African Water Research Commission, 2015)
Acid mine drainage is generated when mining activities expose sulphidic rock to water and oxygen leading to generation of sulphuric acid effluents rich in Fe, Al, SO4 and Mn with minor concentrations of Zn, Cu, Mg, Ca, Pb depending on the geology of the rock hosting the minerals. These effluents must be collected and treated before release into surface water bodies. Mining companies are in constant search for cheaper, effective and efficient mine water treatment technologies. This study assessed the potential of applying magnesite as an initial remediation step in an integrated acid mine drainage (AMD) management system. Neutralization and metal attenuation was evaluated using batch laboratory experiments and simulations using geochemical modelling. Contact of AMD with cryptocrystalline magnesite for 60 min at 1 g: 100 mℓ S/L ratio led to an increase in pH, and a significant increase in metals attenuation. Sulphate concentration was reduced to ≈1 910 mg/ℓ. PH redox equilibrium (in C language) (PHREEQC) geochemical modelling results showed that metals precipitated out of solution to form complex mineral phases of oxy-hydroxysulphates, hydroxides, gypsum and dolomite. The results of this study showed that magnesite has potential to neutralize AMD, leading to the reduction of sulphate and precipitation of metals.
Keywords: Acid mine drainage; Cryptocrystalline magnesite; Geochemical modelling; Toxic metals; Water treatment